Multiple sclerosis and immune system biomarkers: Novel comparison in glatiramer acetate and interferon beta-1a-treated patient groups - Pavelek, Zbysek; Novotny, Michal; Soucek, Ondrej; Krejsek, Jan; Sobisek, Lukas; Sejkorova, Ilona; Masopust, Jiri; Kuca, Kamil; Valis, Martin; Klimova, Blanka; Stourac, Pavel (Multiple sclerosis and related disorders, 2021)
BACKGROUND: Multiple sclerosis (MS) is a chronic, demyelinating disease of the central nervous system (CNS). T cells and B lymphocytes are involved in the development of this disease. METHODS: The following biomarkers were determined in peripheral blood in 28 patients treated with glatiramer acetate (GA) and 21 patients treated with interferon beta 1-a (IFN): IL-10, BAFF, Mx1, IgG, IgG1, IgG2, IgG3 and IgG4 (at baseline and after 6 months of treatment). All participants had confirmed MS diagnosis. OBJECTIVES: The primary objective is to assess a percentual change of biomarkers after 6 months since the first-line treatment initiation with GA or IFN. The secondary objective is to explore correlations between the baseline biomarkers' values (levels). RESULTS: A positive trend was observed in the increase in IL-10 concentration by 30.33 % (IFN) and by 15.65 % (GA). In the IFN group, we observed a statistically significant increase in the BAFF protein concentration by 29.9% (P < 0.001). We found that Mx1 protein levels did not change with the administration of GA, which can be explained by the different mechanisms of action of GA. The serum levels of IgG immunoglobulins and both IgG1 and IgG4 subclasses in both groups of patients were increased. Thus, our data were in accordance with the generally accepted assumption that both IFN and GA are capable of modulating the B cell system. CONCLUSIONS: Our results suggest that treatment with IFN and GA has a more pronounced influence on the B cell system of MS.
Keywords: Humans; Glatiramer acetate; T-Lymphocytes; Multiple Sclerosis; BAFF; IL-10; lidé; Biomarkers; Multiple sclerosis; Glatiramer Acetate; Multiple Sclerosis, Relapsing-Remitting; biologické markery; relabující-remitující roztroušená skleróza; roztroušená skleróza; Mx1; T-lymfocyty; IgG; glatiramer acetát; Interferon beta-1a; interferon beta 1a